A conserved element in the first intron of Cd4 has a lineage specific, TCR signal-responsive, canonical enhancer function that matches the timing of cell surface CD4 upregulation required to prevent lineage choice error - Swan, Gregory A.; Fujii, Chika; Guzynski, Mia E.; Page, Sheridan M.; Meyers, Isabelle V.; Penev, Yordan P.; Littleton, Sejiro; Azzahra, Adinda; Richardson, Christine; Sarafova, Sophia D. (Frontiers in Immunology, 2025)
IntroductionThe regulation of Cd4 expression during T-cell development and immune responses is essential for proper lineage commitment and function in the periphery. However, the mechanisms of genetic and epigenetic regulation are complex, and their interplay not entirely understood. Previously, we demonstrated the need for CD4 upregulation during positive selection to ensure faithful commitment of MHC-II-restricted T cells to the CD4 lineage. In this study, we investigate whether a conserved region, here called NCE, that is proximal to the Cd4 silencer and contains E4m has the required developmental-stage-specific canonical enhancer function and TCR responsiveness to mediate the CD4 upregulation required to prevent lineage errors.MethodsTo investigate the role of NCE, transient transfection of reporter plasmids was performed in thymoma cell lines arrested at the double-positive (DP, CD4+CD8+) and intermediate (INT, CD4+CD8lo) stages of development. CRISPR/Cas9-mediated deletion of the coreNCE/E4m region was carried out in these cell lines to assess its impact on CD4 surface expression, re-expression rates, and TCR signaling responsiveness. To avoid developmental alterations from direct manipulation of the endogenous Cd4 locus in vivo, BAC-transgenic reporter mice were generated with the locus modified to express EGFP in the presence or absence of NCE. EGFP mRNA levels were measured via RT-qPCR, and EGFP fluorescence was analyzed in post-selection thymocytes.ResultsOur in vitro experiments demonstrate that NCE by itself can function as an enhancer at the INT, but not the DP stage of development. Furthermore, CRISPR/Cas9-mediated deletion of coreNCE/E4m resulted in reduced CD4 surface levels, slower re-expression rates, and reduced TCR signaling responsiveness in INT cells, but not in DP cells. In vivo, NCE-sufficient transgenic mice exhibited upregulation of Cd4 reporter EGFP mRNA levels at the INT stage and a corresponding upregulation of EGFP fluorescence, whereas NCE-deficient mice showed a significant loss of Cd4 reporter EGFP mRNA and no detectable EGFP production in any post-selection thymocytes.DiscussionThis study demonstrates that the canonical enhancer function of coreNCE/E4m is essential for CD4 upregulation following positive selection. The NCE region, with its developmental-stage-specific activity and its known epigenetic regulatory capabilities, ensures faithful lineage commitment to the CD4 lineage.